2019
DOI: 10.1002/mrm.27971
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Voxel 1H MR spectroscopy of cerebral nicotinamide adenine dinucleotide (NAD+) in humans at 7T using a 32‐channel volume coil

Abstract: Purpose: Reliable monitoring of tissue nicotinamide adenine dinucleotide (NAD + ) concentration may provide insights on its roles in normal and pathological aging.In the present study, we report a 1 H MRS pulse sequence for the in vivo, localized 1 H MRS detection of NAD + from the human brain.Methods: Studies were carried out on a 7T Siemens MRI scanner using a 32-channel product volume coil. The pulse sequence consisted of a spectrally selective low bandwidth E-BURP-1 90° pulse. PRESS localization was achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 45 publications
5
46
0
1
Order By: Relevance
“…24 A similar TE was achieved for 7 T with a 3D-localizing triple-echo sequence with optimized Shinnar-Le Roux refocusing pulses. 25 The nWE method with the shortest reported TE so far was suggested by Gonçalves et al 28 for use in rat brain at 9.4T. It was similar to our 3D I-CSE method, first reported at about the same time in Ref.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…24 A similar TE was achieved for 7 T with a 3D-localizing triple-echo sequence with optimized Shinnar-Le Roux refocusing pulses. 25 The nWE method with the shortest reported TE so far was suggested by Gonçalves et al 28 for use in rat brain at 9.4T. It was similar to our 3D I-CSE method, first reported at about the same time in Ref.…”
Section: Discussionsupporting
confidence: 83%
“…Instead, to obtain a short TE of 18 ms at 7 T, 1D‐LASER was used to localize a whole slice 24 . A similar TE was achieved for 7 T with a 3D‐localizing triple‐echo sequence with optimized Shinnar‐Le Roux refocusing pulses 25 . The nWE method with the shortest reported TE so far was suggested by Gonçalves et al 28 for use in rat brain at 9.4T.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first 31 P-MRS study to report NAD in the aging human brain found that tNAD, NAD + , and the NAD + /NADH redox ratio decreased with age in the occipital region (Zhu et al, 2015). Similar findings were found for NAD + measured by 1 H-MRS (Bagga et al, 2020), but this was not replicated in a recent 31 P-MRS study in which NAD was not affected by age (Elhassan et al, 2019). When NAD was measured in the frontal lobe of healthy participants (Kim et al, 2017), an age-dependent increase in NADH and decrease in the NAD + /NADH redox ratio was observed, but no change in NAD + was detected.…”
Section: Nad Association With Atp Level and The Influence Of Agesupporting
confidence: 57%
“…This is, in part, caused by the measuring of combined NAD + and NAD, but NADH levels do not account for the multiple orders of magnitude difference observed here. Despite these caveats, the relative change in CSF NAD(H) with age is consistent with later reports on brain NAD + levels [89,90].…”
Section: Humanssupporting
confidence: 87%